Hidden Curriculum, Subject Formation, and Islamic Education in an Aviation Cadet Institution - Abdusshomad, Alwazir; Kalbuana, Nawang; Kurnianto, Benny (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study analyses how the hidden curriculum at Politeknik Penerbangan Indonesia Curug (PPI Curug) shapes cadet subject formation and reframes the practical meaning of Islamic Religious Education (IRE) beyond formal classroom instruction. Using a qualitative case-study design based on critical document analysis, the study examines ten official institutional texts issued or published between 2019 and 2025, including regulations, cadet-care guidelines, strategic documents, academic calendars, dormitory-entry announcements, public-information reports, and official institutional webpages. The data were analyzed through data reduction, thematic coding, data display, and critical interpretation using hidden curriculum theory, Foucault’s concept of discipline and subjectivation, Bourdieu’s habitus and symbolic power, critical pedagogy, and Islamic educational concepts such as adab, amanah, responsibility, and ethical self-formation. The findings show that the hidden curriculum operates through four interrelated mechanisms: the regulation of time, the regulation of space and body, administrative moralization, and humanistic formation. These mechanisms construct the ideal cadet as punctual, orderly, visible, self-monitoring, professionally reliable, and morally legible. The article concludes that IRE in disciplinary vocational institutions is mediated by institutional conditions that translate piety, discipline, responsibility, and professionalism into governable forms of conduct.